9-5x=-x+57

Simple and best practice solution for 9-5x=-x+57 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-5x=-x+57 equation:



9-5x=-x+57
We move all terms to the left:
9-5x-(-x+57)=0
We add all the numbers together, and all the variables
-5x-(-1x+57)+9=0
We get rid of parentheses
-5x+1x-57+9=0
We add all the numbers together, and all the variables
-4x-48=0
We move all terms containing x to the left, all other terms to the right
-4x=48
x=48/-4
x=-12

See similar equations:

| -66-2x=63-8x | | 6v+12=10v | | 7x+4-3x=48 | | 30=-4t^2+24t | | 26+m=5(−6+3m) | | 5y(5y/(2y+5))^2/3=49.5 | | 9(4x+2)=30x | | 4x-13x=-12 | | (a.12)+32=180 | | 2v=-166 | | 35x+70=35x+52 | | -93+3x=-9x+63 | | 85-34=17(5x-2) | | x3=27216 | | (3x^2)+3=16 | | 9n+15+6n=60 | | 5+-9=-3+7t | | 0.6(x-3)=0.8(2x+4) | | 7(x+7)=-7x+7 | | 8(x–1)=8x–8 | | 6-9=5x-10x+2 | | 5=z/3 | | 2(x+1)=5x–3x | | 6-9=5x-10x-2 | | -6u+3(u-7)=3 | | 5x-54=18+2x | | 6-9x=5x-1x-2 | | ((x)^4-8(x)^3+15(x)^2+8x-16)=0 | | k13=-13 | | 8x-7x+4(2x-8)=31 | | 12=a8 | | 44x-11=11(4x-1) |

Equations solver categories